The Quest for Text. Greek Manuscripts and Medieval Latin Translators (Interfaces: A Journal of Medieval European Literatures, 2024)
Medieval translators from Greek had to face an important challenge in getting hold of high quality model texts on which their works could rely. Documentary evidence on the subject is limited: it suggests that the acquisition of Greek manuscripts was often realised as the marginal effect of diplomatic activity. However, the reports of exchanges between monarchs and their envoys likely represent only a fraction of the transfer process of Greek texts and books to the Latin world. The article surveys the available evidence regarding Latin translations of philosophical, theological, and scientific texts from Greek sources from the twelfth through the fourteenth century. Although our knowledge is often tentative and incomplete, the study of the translators' models is rewarding for the insight that they give into the availability of exceptional Greek manuscripts and rare texts in that period.
Keywords: Translations; Greek manuscripts; Philosophy; Medicine; Astronomy